Irritable Bowel Syndrome in Women with Euthyroid Hashimoto’s Thyroiditis: Is There Any Relationship Between Thyroid Autoimmunity and Irritable Bowel Syndrome? - Yeşilova, Aylia; Bilge, Müge; Gökden, Yasemin; Adaş, Mine (Cerrahpaşa Medical Journal, 2022)
Objective: The relationship between euthyroid Hashimoto thyroiditis and irritable bowel syndrome is not well elucidated. The objective of this study is to estimate the rates of irritable bowel syndrome using Rome IV diagnostic criteria in both Hashimoto thyroiditis and control participants and to evaluate the relationship between thyroid autoimmunity and irritable bowel syndrome. Methods: We conducted a cross-sectional study including a total of 480 women; 260 women with Hashimoto thyroiditis and 220 age-matched controls. We evaluated comprehensively the rates of irritable bowel syndrome in Hashimoto thyroiditis patients and controls. We also investigated the features likely to influence the presence of irritable bowel syndrome in women with euthyroid Hashimoto thyroiditis and healthy controls. Results: The frequency of irritable bowel syndrome was 30.7% (n = 80) in Hashimoto thyroiditis patients and 29.5% (n = 65) in controls with no statistically significant differences between the groups (P = .428). Although thyroid antibody titers were higher in Hashimoto thyroiditis with irritable bowel syndrome than in Hashimoto thyroiditis without irritable bowel syndrome, this difference did not reach statistical significance (P = .056). The presence of asthma and depression was associated with increased rates of irritable bowel syndrome in both Hashimoto thyroiditis patients (P = .001 and P = .001) and controls (P = .001and P= .037). Conclusions: In this study, we found that there was no association between euthyroid Hashimoto thyroiditis and irritable bowel syndrome. Although not statistically significant, thyroid antibody titers were higher in Hashimoto thyroiditis with irritable bowel syndrome, and their implications for irritable bowel syndrome development in HT patients remain to be elucidated. Cite this article as: Yeşilova A, Bilge M, Gökden Y, Adaş M. Irritable bowel syndrome in women with euthyroid hashimoto’s thyroiditis: is there any relationship between thyroid autoimmunity and irritable bowel syndrome? Cerrahpaşa Med J. 2023;47(2):123-128.